Naltrexone for the treatment of alcoholism: A meta-analysis of randomized controlled trials - Srisurapanont M. (2014)
Many trials of naltrexone have been carried out in alcohol-dependent patients. This paper is aimed to systematically review its benefits, adverse effects, and discontinuation of treatment. We assessed and extracted the data of double-blind, randomized controlled trials (RCTs) comparing naltrexone with placebo or other treatment in people with alcoholism. Two primary outcomes were subjects who relapsed (including heavy drinking) and those who returned to drinking. Secondary outcomes were time to first drink, drinking days, number of standard drinks for a defined period, and craving. All outcomes were reported for the short, medium, and long term. Five common adverse effects and dropout rates in short-term treatment were also examined. A total of 2861 subjects in 24 RCTs presented in 32 papers were included. For short-term treatment, naltrexone significantly decreased relapses [relative risk (RR) 0.64, 95% confidence interval (CI) 0.51-0.82], but not return to drinking (RR 0.91,95% CI 0.81-1.02). Short-term treatment of naltrexone significantly increased nausea, dizziness, and fatigue in comparison to placebo [RRs (95% CIs) 2.14 (1.61-2.83), 2.09 (1.28-3.39), and 1.35 (1.04-1.75)]. Naltrexone administration did not significantly diminish short-term discontinuation of treatment (RR 0.85, 95% CI 0.70-1.01). Naltrexone should be accepted as a short-term treatment for alcoholism. As yet, we do not know the appropriate duration of treatment continuation in an alcohol-dependent patient who responds to short-term naltrexone administration. To ensure that the real-world treatment is as effective as the research findings, a form of psychosocial therapy should be concomitantly given to all alcohol-dependent patients receiving naltrexone administration. Copyright © 2005 CINP.